Odpowiedzi

2010-01-31T15:07:22+01:00
( - 5 2/3) : (-2 5/6)=-17/3:-17/6=-17/3*-6/17=2

0 :(-1 1/2)=0*-1 1/2=0

(-0,8 ) : 0,5=-8/10:5/10=-8/10*10/5=-8/5=-1 3/5

(-1,2) :(-0,03)=-12/10:-3/100=-12/10*-100/3=40

3,6 : (-0,9)=36/10:-9/10=36/10*-10/9=-4

(-1):2 1/2=-1:5/2=-1*2/5=-2/5

3 1/3 :(-2 2/9)=10/3:-20/9=10/3*-9/20=-1 1/2

(-5 1/3): (-8/11) =-16/3*-11/8=7 1/3

(- 7/2):(-3,5)=-7/2:-35/10=-7/2*-10/35=1
44 3 44
Najlepsza Odpowiedź!
2010-01-31T15:13:09+01:00
(-5 2/3) : (-2 5/6) = (-17/3) * (-6/17) = 2
0 : (-1 1/2) = 0
(-0,8) : 0,5 = (- 8/10) * 2 = -1,6
(-1,2) : (0,03) = (-1 2/10)* (- 100/3) = 40
3,6 : (-0,9) = 3 6/10 * (-10/9) = -4
(-1):2 1/2 = (-1) * 2/5 = (-2/5) = 0,4
3 1/3 :(-2 2/9) = 10/3 * (-9/20) = (-3/2) = -1,5
(-5 1/3): (-8/11) = (-16/3) * (-11/8) = (22/3) = 7 1/3
(- 7/2):(-3,5) = (-7/2) * (-2/7) = 1
71 4 71
2010-01-31T15:16:44+01:00
(-5 2/3): (-2 5/6)=(-17/3):(-17/6)=(-17/3)×(-6/17)=2
0:(-1 1/2)=0
(-0,8):0,5=(-8):5=-8/5
(-1,2):(-0,03)=(-120):(-3)=40
3,6:(-0,9)=36:(-9)=-4
-1:2 1/2=-1:5/2=-1×2/5=-2/5
3 1/3:(-2 2/9)=10/3:(-20/9)=10/3×(-9/20)=-3/2
(-5 1/3):(-8/11)=(-16/3):(-8/11)=(-16/3)×(-11/8)=22/3
(-7/2):(-3,5)=(-7/2):(-35/10)=(-7/2)×(-10/35)=1
26 3 26